2017
DOI: 10.1186/s12915-017-0456-5
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal spine evolution in threespine sticklebacks via a splicing change in MSX2A

Abstract: BackgroundDorsal spine reduction in threespine sticklebacks (Gasterosteus aculeatus) is a classic example of recurrent skeletal evolution in nature. Sticklebacks in marine environments typically have long spines that form part of their skeletal armor. Many derived freshwater populations have evolved shorter spines. Changes in spine length are controlled in part by a quantitative trait locus (QTL) previously mapped to chromosome 4, but the causative gene and mutations underlying the repeated evolution of this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…indicated that length of the first dorsal spine maps to the region containing Msx2a on chromosome IV, and length of the pelvic spine and pelvic girdle map to the Pitx1 region on chromosome VII, consistent with previous work (Chan et al. ; Howes et al ). In the QTL maps within each F 1 family peaks on chromosome IV near Msx2a explained an average of 9% of the variance (PVE) in first dorsal spine length and the peaks on chromosome VII near Pitx1 explained on average 57% of the variance in pelvic spine length, depending on family (see Table for individual F 1 family values).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…indicated that length of the first dorsal spine maps to the region containing Msx2a on chromosome IV, and length of the pelvic spine and pelvic girdle map to the Pitx1 region on chromosome VII, consistent with previous work (Chan et al. ; Howes et al ). In the QTL maps within each F 1 family peaks on chromosome IV near Msx2a explained an average of 9% of the variance (PVE) in first dorsal spine length and the peaks on chromosome VII near Pitx1 explained on average 57% of the variance in pelvic spine length, depending on family (see Table for individual F 1 family values).…”
Section: Resultssupporting
confidence: 90%
“…; Howes et al. ). Future experiments are needed to disentangle individual genetic contributions to divergent evolution.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations